2022
DOI: 10.1039/d2se01109c
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional BiTeI as a novel perovskite additive for printable perovskite solar cells

Abstract: Hybrid organic-inorganic perovskite solar cells (PSCs) are attractive printable, flexible, and cost-effective optoelectronic devices constituting an alternative technology to conventional Si-based ones. The incorporation of low-dimensional materials, such as two-dimensional...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Our previous work has demonstrated that lowering the VBO is advantageous for device performance, as it reduces nonradiative recombination at the interface between the HTL (PTAA) and the perovskite. 88 Moreover, experimental and theoretical studies have emphasized the importance of an absolute energy level offset of approximately 0.2 eV at the PTAA/ perovskite interface. 89 Additionally, a VBO between 0 and −0.18 eV has been identied as the optimum range for efficient hole extraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work has demonstrated that lowering the VBO is advantageous for device performance, as it reduces nonradiative recombination at the interface between the HTL (PTAA) and the perovskite. 88 Moreover, experimental and theoretical studies have emphasized the importance of an absolute energy level offset of approximately 0.2 eV at the PTAA/ perovskite interface. 89 Additionally, a VBO between 0 and −0.18 eV has been identied as the optimum range for efficient hole extraction.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we have demonstrated that the doping of the perovskite with BiTeI nanosheets leads to a modification of the energy levels of the perovskite. 88 In this context, increasing the CBO and decreasing the VBO have proven to be advantageous for device performance. Similar to our previous findings, tuning the CBO and VBO by incorporating TMC interlayers enhances the FF and, thus, the PCE of PSCs, as demonstrated for PSCs containing InSe and SnS 2 nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…66–68 We have shown in our previous work that a “spike” configuration at the perovskite/ETL interface is beneficial for the performance of inverted PSCs. 69…”
Section: Resultsmentioning
confidence: 99%
“…[66][67][68] We have shown in our previous work that a "spike" conguration at the perovskite/ETL interface is benecial for the performance of inverted PSCs. 69 Fig. S12 † shows the normalized SPV spectra of perovskite lms treated with OABr and compared with that of the reference.…”
Section: Steady State and Transient Measurementsmentioning
confidence: 99%
“…40 Additionally, PbI 2 around the GBs acts as a seed to transform the host perovskite lattice into a hexagonal PbI 2 lattice with the release of volatile MA + or FA + cations, eventually lowering the device performance. 41,42 Furthermore, Kymakis et al 43 discussed the interfacial energetic alignment optimization and, by controlling the distribution of charge carriers across the device, the device V oc and FF were improved using BiTeI 2D flakes.…”
Section: Introductionmentioning
confidence: 99%